Understanding University Students’ Digital Literacy in Distance and Face-To-Face Learning - Dewi Wardah Mazidatur Rohmah; Muhammad Dhika Arif Rizqon (MultiTech Publisher, 2024)
For all generations, not just Generation Z, who are often labelled as digital natives, having the skill to use technology appropriately and effectively is essential as it is a vital part of our life. Since we cannot be certain that we have the abilities required to evaluate digital information, understanding digital literacy is even more important in the context of higher education because it helps us to measure and define our skill in using digital information. Therefore, this comparative study aims at measuring the Digital Literacy (DL) of Face-to-Face (FTF) campus students (group 1) and Distance Learning (DLe) campus students (group 2). The Digital Literacy Scale (DLS) was distributed to 500 students at various levels (freshman undergraduates to postgraduates) spread across several campuses in Indonesia which apply Distance Learning or Face-to-Face Learning. The result of the analysis provides an up-to-date overview of the DL abilities of students in relation to their learning and socialization skills during their time as students. Furthermore, we also discuss the implications that indicate how they will continue to adapt to the drastic changes in the era of Industry 4.0.